A biochemical profile of cardiac involvement in perinatal asphyxia - Kumar P., Senthil; Arasan G., Durai (International Journal of Contemporary Pediatrics, 2018)
Background: Perinatal hypoxia is one of the leading causes of mortality and morbidity in developing countries like India, and even in developed countries. Perinatal hypoxia can result in Transient myocardial ischemia, tricuspid and mitral regurgitation, myocardial infarction, cardiac failure. The measurement of Creatine kinase -MB isoenzyme a cardiac specific enzyme helps in assessing the degree of myocardial involvement in asphyxiated infants. Methods: A Prospective case-control study was done in a Tertiary care centre serving rural areas predominantly, to determine the cardiac involvement by measuring serum MB isoenzyme of creatine kinase in perinatally asphyxiated inborn term babies for a period of six months. Results: There was a significant difference in the CK-MB values with regard to weight in both cases and controls. The mean CK-MB levels were higher in babies who had assisted delivery (forceps and breech) than those delivered by labour natural and LSCS. Mean CK-MB values of asphyxiated and controls were 133.8u/l and 27.12 u/l respectively with a p value of < 0.01. There was a significant difference between HIE1 and 3 with a p value of<0.02. Out of 60 cases 28 had abnormal ECG findings (46.6%). Statistically significant difference was found in the mean CK-MB between the normal and Grade4 ECG changes group. The overall predictive accuracy of CK-MB is high in Perinatal asphyxia (88%), Cardiac involvement (83%), Mortality (83%) and a moderate predictive accuracy for HIE (75%). Conclusions: Cardiac abnormalities in asphyxiated neonates are often underdiagnosed and requires high index of suspicion. Cardiac specific enzyme CK-MB helps in early recognition of myocardial damage and better management of cases, would reduce the neonatal mortality and morbidity. An expectant eye can be kept for complications in babies with markedly elevated CK-MB enzyme.